Catcalling awareness among Universitas Pertamina’ students from the perspective of Security Studies - Ramadhan, Iqbal; Sihaloho, Rezya Agnesica Helena (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2021)
This study investigates the dangers of catcalling, which is harmful to women. Catcalling is a form of street sexual harassment that has a negative impact on women's mental health. The goal of this study was to see how well Universitas Pertamina students understood the dangers of catcalling. Pertamina University was chosen as the subject of the study by the author because it is only five years old and has never conducted a survey on catcalling behavior. The author employs a hybrid “explanatory sequential design.”This method was used to collect statistical data from 401 respondents. The statistical data is intended to assess students' understanding of the catcalling phenomenon. The qualitative analysis of this study discusses in the security study using the Copenhagen School Security Study conceptual framework. According to the findings of this survey, one of the most common reasons for women to become victims of catcalling is that they were described as objects (63 percent). Furthermore, 47 percent of respondents understood what catcalling behavior entails. The remainder, or approximately 42 percent of respondents, agreed that catcalling is a bothersome activity. Meanwhile, 68.8 percent of respondents said the way women dressed triggered catcalling. Another 58.9 percent said patriarchal culture was the catalyst for this behavior. The author argues that Universitas Pertamina students already knows catcalling behavior. However, the authors conclude that universities must educate students on catcalling behavior, which stems from patriarchal culture, on a regular basis.